2004
DOI: 10.3200/aeoh.59.1.31-36
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Effluents from a Car Battery Manufacturing Plant in Nigeria on Water, Soil, and Food Qualities

Abstract: The authors investigated the impact of effluents from a car battery manufacturing plant in Nnewi, Nigeria, on water, soil, and food qualities. The authors analyzed heavy metals mercury, arsenic, lead, cadmium and nickel in tap and cassava waters, soil, dried cassava tuber, and edible fruit samples from the company, using an atomic absorption spectrophotometer. Other parameters the authors analyzed include pH, electrical conductivity (EC), salinity (SAL), total hardness (TH), biological oxygen demand (BOD), vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 16 publications
1
18
0
Order By: Relevance
“…The mean Pb concentration (59.13 mg/kg) in soil obtained in this study area falls within the Pb concentration range (38-102 ppm) obtained in the soil around a car battery manufacturing site in Nigeria by Orisakwe et al (2004), 17.07-8469 mg/kg by Yaylali-Abanuz (2011) obtained in surface soil around Gegze industrial area, Turkey but higher than the mean Pb concentrations of 14.13 mg/kg reported by Babatunde et al (2014) in soil in the vicinity of an oil depot in Jos, Nigeria and 47.8 mg/kg by Srinivas et al (2009) in soil within an industrial area, and 18 mg/kg reported by Iyaka and Kakulu (2012b) around a ceramic and pharmaceutical industrial sites in Suleja and Minna, Nigeria. The observed mean Pb level is however much lower than 181 µg/g reported by Iyaka and Kakulu (2012a) from the soil of the vicinity of a local brass industrial area in Bida, Nigeria and 4904 mg/kg reported by Adie and Osibanjo (2009) in soil from an automobile battery company in Ota, Nigeria.…”
Section: Resultsmentioning
confidence: 93%
“…The mean Pb concentration (59.13 mg/kg) in soil obtained in this study area falls within the Pb concentration range (38-102 ppm) obtained in the soil around a car battery manufacturing site in Nigeria by Orisakwe et al (2004), 17.07-8469 mg/kg by Yaylali-Abanuz (2011) obtained in surface soil around Gegze industrial area, Turkey but higher than the mean Pb concentrations of 14.13 mg/kg reported by Babatunde et al (2014) in soil in the vicinity of an oil depot in Jos, Nigeria and 47.8 mg/kg by Srinivas et al (2009) in soil within an industrial area, and 18 mg/kg reported by Iyaka and Kakulu (2012b) around a ceramic and pharmaceutical industrial sites in Suleja and Minna, Nigeria. The observed mean Pb level is however much lower than 181 µg/g reported by Iyaka and Kakulu (2012a) from the soil of the vicinity of a local brass industrial area in Bida, Nigeria and 4904 mg/kg reported by Adie and Osibanjo (2009) in soil from an automobile battery company in Ota, Nigeria.…”
Section: Resultsmentioning
confidence: 93%
“…Though minor variation exists, the concentration of lead of roadside surface soil increases with increase in traffic congestion (Tables 1, 2 and 7) for both years under study. Several small, medium and large scale industrial manufacturing outfits such as electrical cable, battery, plastics, textiles, paper, brewery, vegetable oil, automobile parts manufacturing and assembling; in addition to fertilizer and tyre manufacturing, rubber and timber processing, iron ore, tin smelting and rolling mills as well as crude oil exploration, exploitation and refining that occur in some of the cities of study, can increase the concentration of lead in those cities, and previous reports support this view [28,33,34]. …”
Section: Discussionmentioning
confidence: 91%
“…Through a series of chemical and biochemical processes metals are concentrated and transformed into various products resulting in the amount of the metals being higher than their natural environmental concentration. Lead (Pb) stands out as the most ubiquitous metal in Nigerian environment, caused by automobile emissions [13], industrial effluents [28], paint flakes [11], refuse dumps [9] and electronic wastes [10]. Despite global awareness of the hazardous nature of lead, enforcement of legislation to mitigate lead pollution in Nigeria has not yielded many results.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, high levels of Cd, chromium (Cr), Fe, Zn and Cu have been reported in paint flakes and soil (Nduka et al, 2006(Nduka et al, , 2007(Nduka et al, , 2008Orisakwe et al, 2004). The possible long-term deleterious effects of these heavy metals among occupationally exposed painters in Nigeria have also been reported (Nduka et al, 2007;Orisakwe et al, 2007).…”
Section: Introductionmentioning
confidence: 90%